2016
DOI: 10.1177/1362361316669622
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the reciprocal behaviour of children with autism

Abstract: Differences in the social limitations of girls compared to boys on the autism spectrum are still poorly understood. Impaired social-emotional reciprocity is a core diagnostic criterion for an autism spectrum disorder. This study compares sex differences in reciprocal behaviour in children with autism spectrum disorder (32 girls, 114 boys) and in typically developing children (24 girls, 55 boys). While children with autism spectrum disorder showed clear limitations in reciprocal behaviour compared to typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
33
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 36 publications
6
33
0
2
Order By: Relevance
“…The experimenter prompts the child non‐verbally to contribute meaningful elements to the drawing. The experimenter and the child take turns in drawing, using their own coloured marker (see for more details Backer van Ommeren et al , , in press). For each turn of the child, four scales of reciprocal behaviour are rated: Turn‐taking (one point is awarded if the child copies the experimenter's turn‐taking behaviour), Reciprocal interaction (one point is awarded if the child adds meaningful elements to a shared drawing object), Reciprocal interaction in the other's initiative (one point is awarded if the child contributes to objects initiated by the experimenter) and Reciprocal flexibility (one point is awarded if the child accepts a specific interfering input of the experimenter in his or her own drawing object).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimenter prompts the child non‐verbally to contribute meaningful elements to the drawing. The experimenter and the child take turns in drawing, using their own coloured marker (see for more details Backer van Ommeren et al , , in press). For each turn of the child, four scales of reciprocal behaviour are rated: Turn‐taking (one point is awarded if the child copies the experimenter's turn‐taking behaviour), Reciprocal interaction (one point is awarded if the child adds meaningful elements to a shared drawing object), Reciprocal interaction in the other's initiative (one point is awarded if the child contributes to objects initiated by the experimenter) and Reciprocal flexibility (one point is awarded if the child accepts a specific interfering input of the experimenter in his or her own drawing object).…”
Section: Methodsmentioning
confidence: 99%
“…It is evident that in both ASD and ID individuals, impairments in social interactions are to be found (DSM‐5). Within this domain, recent studies have indicated that limitations in reciprocity can be measured reliably and are clearly linked to ASD in normally intelligent children (Backer van Ommeren et al ; Backer van Ommeren et al , in press). It is currently unknown whether these limitations may also be indicative for ASD in children with ID.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This notion is reenforced by several studies in this Special Issue that went beyond the use of standardised diagnostic tools, employing novel measures that tap key constructs. Backer van Ommeren et al (2017) use a sensitive and ecologically valid paradigm, the Interactive Drawing Test, to measure social reciprocity. In so doing, they were able to tease out strengths and difficulties of autistic girls that would have been invisible had they used cruder, ordinary diagnostic measures.…”
mentioning
confidence: 99%